Integrative non-pharmacological care for individuals at risk of rheumatoid arthritis - Courel-Ibáñez, Javier; Vetrovsky, Tomas; Růžičková, Nora; Marañón, Concepción; Durkalec-Michalski, Krzysztof; Tomcik, Michal; Filková, Mária (Rheumatology international, 2024)
There is increasing knowledge in the recognition of individuals at risk for progression to rheumatoid arthritis (RA) before the clinical manifestation of the disease. This prodromal phase preceding the manifestation of RA may represent a "window of opportunity" for preventive interventions that may transform the clinical approach to this disease. However, limited evidence exists in support of effective interventions to delay the onset or even halt the manifestation of RA. Given the multifactorial nature of RA development and disease progression, the latest guidelines for established RA stress the use of integrative interventions and multidisciplinary care strategies, combining pharmacologic treatment with non-pharmacological approaches. Accordingly, individuals at risk of RA could be offered an integrative, multifactorial intervention approach. Current data point toward pharmacological intervention reverting the subclinical inflammation and delay in the disease onset. In addition, targeting life style modifiable factors (smoking cessation, dental health, physical activity, and diet) may presumably improve RA prognosis in individuals at risk, mainly by changes in epigenetics, autoantibodies, cytokines profiles, and microbiome. Nonetheless, the benefits of multidisciplinary interventions to halt the manifestation of RA in at-risk individuals remain unknown. As there is a growing knowledge of possible pharmacological intervention in the preclinical phase, this narrative review aims to provide a comprehensive overview of non-pharmacological treatments in individuals at risk of RA. Considering the mechanisms preceding the clinical manifestation of RA we explored all aspects that would be worth modifying and that would represent an integrative non-pharmacological care for individuals at risk of RA.
Keywords: Exercise; Autoantibodies; zánět; Holistic care; Rheumatoid arthritis; prognóza; lidé; autoprotilátky; Nutrition; revmatoidní artritida; Life Style; Prevention; Arthritis, Rheumatoid; Microbiota; Humans; Inflammation; životní styl; Prognosis